2016
DOI: 10.1002/2015jb012677
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotelluric investigation of the Vestfold Hills and Rauer Group, East Antarctica

Abstract: The Vestfold Hills and Rauer Group in East Antarctica have contrasting Archean to Neoproterozoic geological histories and are believed to be juxtaposed along a suture zone that now lies beneath the Sørsdal Glacier. Exact location and age of this suture zone are unknown, as is its relationship to regional deformation associated with the amalgamation of East Gondwana. To image the suture zone, magnetotelluric (MT) data were collected in Prydz Bay, East Antarctica, mainly along a profile crossing the Sørsdal Glac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 76 publications
2
13
0
Order By: Relevance
“…Although theoretical considerations suggest that departures from the MT plane-wave source-field assumption may be prevalent at the poles due to the presence of the polar atmospheric electrojets (Pirjola, 1998), Beblo and Liebig (1990) showed that MT impedance responses from different time segments remain stationary despite clear variations in source strength associated with the electrojet. This conclusion is also supported by the lack of source-effect complications in more recent datasets others, 1996, 2004;Peacock and Selway, 2016).…”
Section: Previous Em Surveys In Antarcticasupporting
confidence: 68%
See 2 more Smart Citations
“…Although theoretical considerations suggest that departures from the MT plane-wave source-field assumption may be prevalent at the poles due to the presence of the polar atmospheric electrojets (Pirjola, 1998), Beblo and Liebig (1990) showed that MT impedance responses from different time segments remain stationary despite clear variations in source strength associated with the electrojet. This conclusion is also supported by the lack of source-effect complications in more recent datasets others, 1996, 2004;Peacock and Selway, 2016).…”
Section: Previous Em Surveys In Antarcticasupporting
confidence: 68%
“…Due to the high resistivity of firn, the contact resistance of the electric bipoles used to measure the telluric fields can be as high as 1 MΩ leading to enhanced capacitive coupling with the ground, and so specialized ultra-high-input impedance buffer amplifiers and electrodes must be used to minimize these effects (Zonge and Hughes, 1985). Wannamaker and others (2004) and Peacock and Selway (2016) have demonstrated the effectiveness of this approach for measuring electric fields in Antarctica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MT method assumes that the Earth's magnetic field behaves as a homogeneous plane wave (Cagniard, 1953), but in auroral regions close to the magnetic poles, this assumption may break down (e.g., Hill, 2020; Jones & Spratt, 2002; Peacock & Selway, 2016; Smirnov & Egbert, 2012). We calculated impedance tensors through separate processing of daytime and nighttime data for the long‐period station and found no evidence of temporal changes in the source field (Figure 2b), suggesting that the data are not impacted by non‐planar source field effects.…”
Section: Datamentioning
confidence: 99%
“…MT results local to the largest population centre Longyearbyen identified a conductivity structure which is suggested as favourable for geothermal heat storage with a zone of high conductivity in the mid-crust 'sealed' by overlying and surrounding resistive bodies . Elevated heat flow rates ranging from 80 to 130 mW m −2 have been reported for the area (Vagnes and Amundsen 1993;Khutorskoi et al 2009;Slagstad et al 2009;Pascal et al 2011) due to local deep faulting, and a thinned (~ 100 km) lithosphere (Bergh and Grogan 2003) combined with the local conductivity structure makes further evaluation of the areas geothermal resource potential warranted. Further a near-surface resistive layer extending to a depth of ~ 120 m represents the permafrost zone of primarily unconsolidated gravels ; however, there is significant heterogeneity in the thickness of the permafrost layer with a max depth of ~ 250 m and a general thinning westward (towards the coast).…”
Section: Svalbard Archipelago Norwaymentioning
confidence: 99%